Microsatellite Marker for Cross-Species Amplification: Study Case for Indonesian Sundaland Python (Serpentes: Pythonidae) - Maulidi, Andri; Fatchiyah, Fatchiyah; Hamidy, Amir; Kurniawan, Nia (Graduate School, Universitas Brawijaya, 2018)
The python of Indonesian Sundaland has been traded for its distinct skin colour and patterns. The need for rapid method in cross-species amplification for Indonesian Sundaland python is useful to contribute in management of sustainability harvesting system. In this research, we screened 10 microsatellite primers which are previously used for Australian, New Guinean, Chinese and Burmese pythons and 7 potentially amplifiable primers for African and Asian reptiles. Python breitensteini showed a greater number of alleles (2-8 alleles) than Python bivittatus (1-3 alleles) and Python brongersmai (1-2 alleles). The observed and expected heterozygosity for all species were ranged from 0 to 1.00 and 0 to 0.79, respectively. According to the high cross-species amplification rates, 15 out of 17 primers were useful in assessing the genetic diversity and conservation genetic of Indonesian Sundaland python. Among the 15 primers, MS3 generated the highest number of allele for P. breitensteini (8 alleles), P. bivittatus (3 alleles), and P. brongersmai (2 alleles). We proposed MS3 locus as a suitable marker for Indonesian Sundaland python.Keywords: microsatellite, Python, Sundaland.